الضرائب والرسوم: دراسة فقهية مقارنة - الشيخ، أحمد بن هلال (جامعة الملك عبدالعزيز, 2020)
تهدف الدراسة إلى بيان الصورة الكاملة عن الضرائب والرسوم، وذلك من خلال المطالب التالية: المطلب الأول جاء عن حقيقة الضرائب والرسوم، والألفاظ ذات الصلة، والمطلب الثاني وضحت فيه الفرق بين الضرائب والرسوم والزكاة، والمطلب الثالث تحدثت فيه عن نشأة الضرائب وتطورها التاريخي، والمطلب الرابع وضحت فيه أنواع وخصائص الضرائب والرسوم والهدف منهما، والمطلب الخامس بينت فيه وعاء الضريبة وأثر تطبيق الضريبة والرسوم في التنمية الاقتصادية، والشروط الواجب مراعاتها عند فرض الضريبة، ثم ختم البحث بالمطلب السادس الذي وضح فيه حكم فرض الضرائب في الفقه الإسلامي.
Praise be to Allah, Lord of the Worlds, and May Allah’s blessing and peace be upon His Messenger Muhammad, the Seal of the Messengers, and his family and companions as a whole: The study aims to show the full picture of taxes and fees in Shari’a, through the following demands: The first demand is about the reality of taxes and fees, and related terms; the second demand clarifies the difference between taxes, fees and zakat; the third demand is about the origin of taxes and their historical development; the fourth requirement classifies the types and characteristics of taxes and fees and the aim thereof; and the fifth demand or requirement indicates to the scale of tax and the impact of the application of tax and fees on economic development, as well as the conditions to be observed when imposing the tax; and then, the research study concludes with the sixth requirement in which the rule of imposing taxes in Islamic jurisprudence was clarified.
Keywords: الأنظمة الضريبية -- الشريعة الإسلامية -- الفقه الإسلامي -- التنمية الاقتصادية -- الاقتصاد الإسلامي